Electrochemical reduction of CO2 to Formic Acid on Pb-Sn Alloy Cathode. Issue 1 (April 2020) - Widiatmoko, Pramujo; Nurdin, Isdiriayani; Devianto, Hary; Prakarsa, Budi; Hudoyo, Henry
Abstract: Carbon dioxide released to the atmosphere due to fossil combustion needs to be reduced to decrease the global warming effect. Electrochemical reduction of CO2 is one of promising technology to convert CO2 to various valuable compounds, reducing the amount of released CO2 to the atmosphere. Metal alloys are interesting material for cathode. In this preliminary work, a CO2 electrochemical reduction was performed on a Pb-Sn alloy cathode using catholyte of KHCO3 and NaHCO3 at various concentrations. An anode from Pt-Ir and H2 SO4 0.1 M as anolyte were used in the experiment. The CO2 was bubbled into 400 mL catholyte at rate of 75 mL min -1 . It was found that Pb-Sn alloy in KHCO3 electrolyte provides higher productivity and faradaic efficiency than in NaHCO3 . Increasing overpotential from 0.1 V to 1 V increases both formic acid productivity and efficiency. The optimum amount of formic acid produced was 9400 μmol in catholyte KHCO3 0.5 M with faradaic efficiency of 67.19% and conversion of 0.326%.